An analysis of U.S. Custom and Border Protection’s tripartite Mexico border security policy - Garrett, Terence M. (Annales. Etyka w Życiu Gospodarczym, 2019)
The Custom and Border Protection (CBP) border security policy was explicitly presented by former Acting Commissioner of CBP, David Aguilar, in testimony before the United States Senate Homeland Security and Governmental Affairs Committee (HSGAC) on April 4, 2017 in testimony on the subject of “Fencing Along the Southwest Border.” Important for discussion here are the key components of the DHS/CBP/Border Patrol’s strategy, or sets of policies, laying forth elements of the border walls (including barriers, fences), personnel, and technology in order to hinder, or intercept, undocumented migrants (homo sacer) from entering the United States illegally—all socially constructed. Aguilar notes in his opening remarks “Maintaining a safe and secure environment along the U.S.—Mexico border is critical. A safe and orderly border that is predicated on the strong rule of law deprives criminal organizations, drug cartels, and criminal individuals the opportunity to thrive.” In Aguilar’s testimony, when pressed by Ranking Member Senator Claire McCaskill, he set forth the current needs for CBP/Border Patrol priority of the three elements in the following order: (1) Technology (border surveillance), (2) Personnel (numbers of agents along the border), and, (3) The Border Wall (physical infrastructure: fences, walls, and vehicle barriers). The security apparatus affects dwellers along the Rio Grande and undocumented border crossers, demonstrated here with an analysis of the application of President Trump’s Zero Tolerance policy (April 6–June 20, 2018). The security framework applied in this paper will consist of theoretical approaches assessing border surveillance as a panopticon, the use of Border Patrol agents for apprehending, detaining and removing homo sacer, and the symbolism of the border wall as a spectacle and simulacrum—all understood in the pursuit of USA border security policy.